A study of respiratory distress in patients with bilateral lung opacities admitted in a tertiary care hospital - Nagar, Mahendra; Saxena, Anil; Khangarot, Suman; Bansiwal, Babulal; K. V., Anees; Phulwari, Jitendra (International Journal of Advances in Medicine, 2017)
Background: Patients presented with respiratory distress along with bilateral lung opacities, like infections, Neoplasia, primary abnormality of the airways, pulmonary edema, pulmonary haemorrhage, acute respiratory distress syndrome, and interstitial lung diseases is a common scenario in our hospitals. The chest radiograph remains the basic radiological tool in many rural hospitals in our country. Thus, we aimed to study the patients presenting with respiratory distress having bilateral opacities in chest radiograph admitted in a tertiary care centre. Methods: This study was cross sectional study conducted in the department of respiratory medicine, New Medical College and Hospital, Kota for a period of one year on indoor patients. Fifty patients were studied by detailed clinical history, thorough physical examination, chest x-ray, routine haematological, sputum, electrocardiogram and relevant investigations. Results: Amongst 50 patients we found tuberculosis in 32% cases, pneumonia in 28%, pulmonary edema in 16%, silicosis (ILD) in 8 %, fungal pneumonia in 8 %, malignancy in 4% and aspiration pneumonia in 4% cases. Conclusions: Patients presenting with respiratory distress and bilateral lung opacities can have different diagnosis, most of them can be diagnosed by thorough history, clinical examinations and basic investigations. Proper diagnosis is essential in these patients for their management.